0124 A Prefrontal-Amygdala Network Model of the Cellular and Circuit-Level Mechanisms of Emotional Memory Consolidation During the Awake State and REM Sleep. (27th May 2020) - Rho, Y; Vijayan, S
Abstract: Introduction: Rapid eye movement (REM) sleep has been implicated in the consolidation of emotional memories. Our recent work found a candidate system for REM-related memory consolidation. We showed that during REM sleep, the frontal cortices are dominated by theta (4–8 Hz) oscillations and bursts of beta (15–35 Hz) activity. Studies suggest that rhythmic interactions between the frontal cortices and limbic structures, in particular the amygdala, play a critical role in the consolidation of emotional memories. However, the mechanisms responsible for memory consolidation during these rhythmic interactions during REM sleep remain unknown. Methods: We used biophysically based neural models to build a large-scale network model of the prefrontal cortex (PFC) and amygdala (AMY) and incorporated synaptic plasticity mechanisms, such as spike-timing dependent plasticity (STDP), into the connections between these two regions. Norepinephrine (NE) and serotonin (SE) levels were manipulated to mimic the different physiological conditions during the awake state and REM sleep. Results: We were able to reproduce the oscillatory dynamics observed in experimental studies and identify cell-type specific synaptic changes caused by STDP. During the awake state, PFC connections to all cell types of the AMY become strengthened when PFC neurons provide theta frequency inputs, with the connections strengthening to a greater extent when inputs are in burst mode rather than single spike mode. When the PFC provides beta inputs, we see the exact opposite relationship: synaptic strengths become weaker when inputs are in burst mode rather than single spike mode. During REM sleep conditions, the connections to all principal cell types of the AMY become strengthened, with synaptic connections to some subtypes of pyramidal cells becoming stronger than others. Surprisingly, however, the synaptic connections to the interneurons become weaker in response to theta frequency inputs. Conclusion: Using our large-scale network model, we show how the levels of the neurotransmitters NE and SE during the awake state and REM sleep affect oscillatory dynamics and in turn influence the strengthening or weakening of connections related to emotional memories. Support: United States Army Research Office, Award number ARO W91lNF-17-1-0300